2019
DOI: 10.3171/2018.4.jns172537
|View full text |Cite
|
Sign up to set email alerts
|

Management of severe intraoperative hemorrhage during intraventricular neuroendoscopic procedures: the dry field technique

Abstract: OBJECTIVEThe unexpected intraoperative intraventricular hemorrhage is a rare but feared and life-threatening complication in neuroendoscopic procedures because of loss of endoscopic vision. The authors present their experience with the so-called “dry field technique” (DFT) for the management of intraventricular hemorrhages during purely endoscopic procedures. This technique requires the aspiration of the entire intraventricular CSF to achieve clear visualization of the bleeding source.METHODSMore than 500 neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Another technique is the dry field technique described by Oertel et al, in which the entire CSF is carefully aspirated to better identify the source of bleeding. Furthermore, gravity and air exposure promotes hemostasis [ 27 ]. In addition, large tumor dimensions can also obscure the view, making it difficult for the surgeon to navigate.…”
Section: Discussionmentioning
confidence: 99%
“…Another technique is the dry field technique described by Oertel et al, in which the entire CSF is carefully aspirated to better identify the source of bleeding. Furthermore, gravity and air exposure promotes hemostasis [ 27 ]. In addition, large tumor dimensions can also obscure the view, making it difficult for the surgeon to navigate.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, with the help of more accurate instruments and neuronavigation methods, endoscopic hematoma evacuation can be conducted under the guidance of visualization of ventricles. Previous reports have shown that patients with IVH treated by endoscopic management tend to have more favorable outcomes, a shorter recovery time[ 3 , 7 , 10 ], and a lower incidence of infection[ 11 ]. Generally, subdural effusion, intraventricular hemorrhage and infection are the main complications in endoscopic procedure, which is similar with conventional indwelling ventricular drainage tube operation.…”
Section: Discussionmentioning
confidence: 99%
“…In endoscopic surgery, vision can be severely restricted even by slight bleeding. Based on our experience and the existing literature, various techniques for hemorrhage control exist, including excessive rinsing, monopolar coagulation, using the heat intensity provided by the light of the endoscope, creating a "fluid chamber" using the trocar or peel-away sheath ("small-chamber irrigation technique"), or using the dry field technique by sucking the CSF out of the ventricles to identify and coagulate the source of bleeding and the air environment also supports the clot formation [19][20][21][22]. These techniques might not suffice for very vascularized lesions compared to microscopic surgery techniques, since forceps for coagulation and adequate suction are not available for neuroendoscopic surgery.…”
Section: Management Of Intraoperative Hemorrhagementioning
confidence: 99%